2012
DOI: 10.1161/strokeaha.112.657288
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Anosognosia for Spatial Neglect After Stroke

Abstract: Background and Purpose-The present study investigated the lesion anatomy of anosognosia for visuospatial neglect resulting from right hemispheric stroke. Methods-In 63 patients, self-ratings of performance in paper-and-pencil tests were contrasted with external performance ratings. Lesion analysis was conducted on patient subgroups with different degrees of anosognosia but comparable visuospatial impairment. Results-Independent of the severity of visuospatial neglect per se, damage to the right angular and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 12 publications
4
25
1
Order By: Relevance
“…However, after correction for age and education years, these neuropsychological findings became insignificant. The data thus support previous reports that identified age as an important contributing factor to the development of ISA (Appelros et al, 2007;Vossel et al, 2012).…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…However, after correction for age and education years, these neuropsychological findings became insignificant. The data thus support previous reports that identified age as an important contributing factor to the development of ISA (Appelros et al, 2007;Vossel et al, 2012).…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In contrast, advanced lesion methods apply specific statistical tests (Rorden and Brett, 2000; Rorden et al, 2007). For group comparisons, the Liebermeister test (e.g., (Vossel et al, 2012)) was found to be more sensitive than the formerly used chi-square test (e.g., (Weiss et al, 2008)). These tests when properly applied reveal the brain regions that are significantly more affected in the patient group suffering from a given cognitive impairment when compared to a patient group unaffected by that cognitive impairment.…”
Section: Methodsmentioning
confidence: 89%
“…Studies indicate that there are regions of the brain that are associated with different types of anosognosia (Pia, Neppi-Modona, Ricci, & Berti, 2004; Rousseaux, Allart, Bernati, & Saj, 2015; Starkstein et al, 2010; Vocat, Staub, Stroppini, & Vuilleumier, 2010; Vossel et al, 2012). Neuroanatomical relationships to neglect subtypes (e.g.…”
Section: Discussionmentioning
confidence: 99%